6r-39=5r-8(-6r-1)

Simple and best practice solution for 6r-39=5r-8(-6r-1) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6r-39=5r-8(-6r-1) equation:


Simplifying
6r + -39 = 5r + -8(-6r + -1)

Reorder the terms:
-39 + 6r = 5r + -8(-6r + -1)

Reorder the terms:
-39 + 6r = 5r + -8(-1 + -6r)
-39 + 6r = 5r + (-1 * -8 + -6r * -8)
-39 + 6r = 5r + (8 + 48r)

Reorder the terms:
-39 + 6r = 8 + 5r + 48r

Combine like terms: 5r + 48r = 53r
-39 + 6r = 8 + 53r

Solving
-39 + 6r = 8 + 53r

Solving for variable 'r'.

Move all terms containing r to the left, all other terms to the right.

Add '-53r' to each side of the equation.
-39 + 6r + -53r = 8 + 53r + -53r

Combine like terms: 6r + -53r = -47r
-39 + -47r = 8 + 53r + -53r

Combine like terms: 53r + -53r = 0
-39 + -47r = 8 + 0
-39 + -47r = 8

Add '39' to each side of the equation.
-39 + 39 + -47r = 8 + 39

Combine like terms: -39 + 39 = 0
0 + -47r = 8 + 39
-47r = 8 + 39

Combine like terms: 8 + 39 = 47
-47r = 47

Divide each side by '-47'.
r = -1

Simplifying
r = -1

See similar equations:

| y=-5y-17 | | 3x^2+10x+11=0 | | 28-4x= | | 17-.33(27y+24)=-10y-11 | | (7x)=(4x) | | .1x^2+54x=1000 | | 9x-21=-45+x | | 400(t)=0.1t^2+3t | | 3x-8=-6x-20 | | -2+v+4= | | log(8-4X)=logX | | y=-33+4x | | .1x^2+49x=1500 | | h(t)=-16t^2+64t+250 | | 5y-29=-26+8y | | 100=2(300)/6 | | 5.5+0.5y=-11+2x | | h=30.4-7t-4.9t^2 | | -9r^2+4s^2=0 | | 0=-16t^2-29t+328 | | 4(3x-8)-3=4(x-2)+21 | | 3=30+30 | | 49x^2+5x=1500 | | 24x+66=-66+27x | | f(2)=7-5 | | 4(3x-2)+27=6x+1 | | 27+x+44=180 | | 400=0.05(x-520) | | 5x-9y=-15 | | -23=4x-6x | | 1.1p+14=16 | | 5(3x-9)-6=5(x-3)+24 |

Equations solver categories